Effects of repeated eccentric contractions with different loads on blood circulation and collagen fiber orientation in the human Achilles tendon - Tomonobu Ishigaki; Toshihiro Ikebukuro; Keitaro Kubo (Japanese Society of Physical Fitness and Sports Medicine, 2018)
The purpose of this study was to compare changes in blood circulation and collagen fiber orientation in the Achilles tendons after repeated eccentric contractions (ECC) with different loads. Thirteen healthy male subjects performed two ECC protocols with different loads and then remained relaxed for 40 min after ECC. Each leg was randomly allocated to low-load protocol (180 repetitions at 50% of one repetition maximum [1RM]) and high-load protocol (75 repetitions at 120% of 1RM). Before and after ECC, blood volume and oxygen saturation in the Achilles tendons were measured using a laser oxygenation monitor. Tendon collagen fiber orientation was also estimated from the coefficient of variation (CV) of echogenicity on transverse ultrasonic images of the Achilles tendon. In the low- and high-load protocols, blood volume in the tendon was significantly higher than the resting level until the end of the recovery period, although oxygen saturation returned to the resting level at the 20-min point of recovery. The CV of echogenicity was significantly lower than the resting level until the end of the recovery period. No differences in the changes in these variables were observed between the two protocols. These results suggest that blood volume and collagen fiber orientation in tendons are changed to the same degree by repeated eccentric contractions with the same amount of work regardless of the magnitude of the load.